The Number and Regional Distribution of Chinese Monks after the Mid-Qing Dynasty - Zhang, Xuesong (Religions, 2023)
The total number of ordination certificates issued between 1736 and 1739 was 340,112. Analyzing the amount and regional distribution of ordination certificates during the early Qianlong period is helpful for us in clarifying the amount and regional distribution of Chinese monks since the mid-Qing Dynasty. The total number of Buddhist monks did not change measurably during the two hundred years from Qianlong’s reign until the Republic period, remaining between 600,000 and 700,000. Although the census in the 1930s did not cover Taoist monks, as previously discussed, their number may have been similar to that during Qianlong’s reign. As a result, the number of monks (both Buddhist and Taoist) did not changed much after the mid-Qing Dynasty, despite many historical changes since the 19th century, such as population growth, the Taiping Heavenly Kingdom Movement, the promotion of education with temple property, and the warlord conflicts. The number of Buddhist monks in Northern China declined significantly from 1742 to 1936, while that in the regions along the midstream and downstream of the Yangtze River and in Southwestern China, it increased significantly. However, the geographical layout of Chinese Buddhism did not changed much, as there was neither a noticeable decline nor a noticeable revival in the number of monks and nuns.